Lunar Sosigenes IMP as analyzed with orbital spectrophotometry and polarimetry - Yuriy Shkuratov; Vadym Kaydash; James Head; Kilho Baek; Sungsoo S. Kim; Sergey Velichko; Yehor Surkov; Minsup Jeong; Young-Jun Choi; Chae Kyung Sim; Hao Zhang; Han Zheng; et al. (Icarus, 2026)

The Maskelyne irregular mare patch as interpreted with lunar optical data, including Danuri polarimetric measurements - Yuriy Shkuratov; Vadym Kaydash; James Head; Kilho Baek; Sungsoo S. Kim; Le Qiao; Sergey Velichko; Yehor Surkov; Nickolay Opanasenko; Minsup Jeong; Young-Jun Choi; Chae Kyung Sim; et al. (Icarus, 2026)

Machine learning derived abdominal aortic calcification is associated with physical frailty in community-dwelling adults: the UK Biobank Imaging Study - Abadi K. Gebre; Marion Mundt; Elsa Dent; James Webster; Afsah Saleem; Syed Zulqarnain Gilani; Yuandan Zhang; Cassandra Smith; Parminder Raina; John P. Kemp; William D. Leslie; John T. Schousboe; et al. (GeroScience, 2026)

Mesoscale eddies in the subpolar North Atlantic: their ecological importance and conservation significance - Lea-Anne Henry; Jason Cleland; Anna Gebruk; René Schubert; Alice Della Penna; Peter Gaube; Christian Mohn; Brynn Devine; Arne Biastoch; Camille M.L.S. Pagniello; Keno Ferter; George Wolff; et al. (Progress in Oceanography, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Characterization of the surface of the Ina irregular Mare patch: A synthesis of lunar optical data, including Danuri polarimetric measurements - Yuriy Shkuratov; Vadym Kaydash; James Head; Kilho Baek; Sungsoo S. Kim; Nickolay Opanasenko; Yehor Surkov; Minsup Jeong; Young-Jun Choi; Chae Kyung Sim; Dukhang Lee; Michael Kreslavsky; et al. (Icarus, 2026)

Ensuring consistent data quality for environmental rating ecolabels with representative secondary datasets - Maëlys Courtat; P. James Joyce; Sarah Sim; Mohamad Kaddoura; Jhuma Sadhukhan; Richard Murphy (The International Journal of Life Cycle Assessment, 2025)
Purpose Environmental rating ecolabels (ERE) are developing rapidly across Europe, intending to guide sustainable purchasing choices through performance ratings derived from life cycle assessment (LCA). Integrating robust data quality methods in the LCA modelling stage is essential for accurate and comparable ratings, but challenging as ERE must be feasible to generate with reasonable effort for broad adoption. The use of secondary life cycle inventory (LCI) datasets, alongside actual product information such as bills of materials, is inevitable. However, the selection process for secondary LCI datasets and its implications for environmental ratings have yet to be investigated. Methods We examine the context-dependent suitability of secondary LCI datasets (aka their representativeness), hypothesising that differing levels of representativeness could lead to differences in product ratings. In a case study involving 94 laundry detergent products, we investigate how different secondary dataset choices influence the resulting aggregated LCA results (single scores), relative product rankings, and environmental ratings. Four distinct data scenarios are defined, in which the production of 19 key ingredients is represented through datasets of varying representativeness (from most specific to most generic). Results Over 60% of the products studied obtained a different rating under at least one of the three lower representativeness (more generic) data scenarios explored as compared with the rating obtained when the highest representativeness (most specific) data scenario was used. Lower representativeness scenarios also led to wider distributions of product single scores, with scenarios which utilised LCI data representing the function of ingredients (e.g. alkalinity source) or generic LCI data (e.g. organic chemicals) showing the most significant deviations from the distributions under the specific data scenario. This highlights the importance of having clearly defined, consistent data quality management approaches for the LCA stage of ERE. Conclusions Product information (e.g. formulation and packaging specifications) from primary sources should be combined with representative LCI datasets from third party databases to obtain reliable product ratings. We demonstrate that the representativeness of secondary datasets can be evaluated through three contextual indicators of data quality (technological, geographical, and temporal representativeness) to help guide the data selection process aligned to defined data quality thresholds. Based on our findings, practical recommendations are provided for data quality management in ERE. Scheme developers are encouraged to embed these in their methodologies to underpin transparent, robust labelling for product comparison.

Environmental rating ecolabels: How does product categorization affect product ratings and potential interpretation? - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; David Sheffield; Richard Murphy (Journal of Industrial Ecology, 2025)
Environmental rating ecolabels (ERE) aim to present aggregated product environmental information to inform consumer choices. Performance ratings (e.g., A–E) are derived from life cycle assessment (LCA) results to enable comparison between products. The translation of LCA results to performance ratings requires definition of a common rating scale, either at a sector level or for subsets of products grouped by function (i.e., product categories). We investigate if and how assigning products to distinct categories influences final product ratings in ERE schemes. We consider if product categorization enables increased product differentiation and how the structure of categories affects the ratings awarded to products. Using a food sector case study, ratings were assigned to 2253 products based on aggregated environmental single scores derived from Agribalyse 3.1 and ratings obtained under three scenarios were compared: (1) no categorization—all products are placed on a single scale before rating; (2a) food group categorization—products are assigned to 11 food groups described in the Ciqual food composition database; and (2b) food subgroup categorization—products are assigned to 61 Ciqual food subgroups. We find that categorization has a significant influence on the final ratings, affecting at least 54% of products evaluated. Categorization restricts the range of products that can be compared but does not systematically improve differentiation within categories. For categorization to be used in ERE, categorization hierarchies need to be developed and harmonized at sector level reflecting consumer‐relevant substitution options. This study demonstrates that categorization is a key methodological consideration for ERE scheme developers.

Environmental rating ecolabels: Considerations for establishing a rating scale with categorical performance classes - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; Richard Murphy (Journal of Cleaner Production, 2025)

Development of GMP compliant cryopreservation for anopheles stephensi mosquitoes supporting manufacture of plasmodium falciparum sporozoite products - Eric James; Tales Vicari Pascini; Jeremy Guth; Ehud Inbar; Swagatika Swain; James Overby; Steven Matheny; Dimitri Koutzoumis; Igor Sharakhov; Najib El-Sayed; Ashton Belew; Kim Lee Sim; et al. (Cryobiology, 2024)

Prospective life cycle assessment of climate and biodiversity impacts of meat‐based and plant‐forward meals: A case study of Indonesian and German meal options - Sandra G. Marquardt; P. James Joyce; Giles Rigarlsford; Mariska Dötsch‐Klerk; Kathelijn van Elk; Jonathan Doelman; Vassilis Daioglou; Mark A. J. Huijbregts; Sarah Sim (Journal of Industrial Ecology, 2024)
The emerging field of prospective life cycle assessment (pLCA) offers opportunities for evaluating the environmental impacts of possible future consumption shifts. One such shift involves a transition from meat‐based to plant‐forward diets, acknowledged to mitigate environmental impacts of the food system under present day conditions. Current diets are often meat intensive (“meat‐based”), whilst “plant‐forward” diets include mainly plant‐based foods, encompassing flexitarian, vegetarian, and vegan diets. Here we illustrate the application of pLCA in a case study of meal options, implementing shared socio‐economic pathway scenarios in the LCA background system to represent future production conditions. We assess the climate footprints and land‐based biodiversity footprints of a typical meat‐based meal in Germany and Indonesia compared to a plant‐forward meal in both countries (i.e., four meals), now and in 2050. Our findings show that the plant‐forward alternative maintains a lower impact per serving in all future scenarios. At the same time, the reduction in impact for the meat‐based meals is more pronounced in future scenarios due to shifts in the agricultural system. Our findings highlight the importance of supply‐side measures to produce lower‐impact ingredients, complementing demand‐side interventions to reshape food consumption. Results are further evaluated in cultural and nutritional contexts, highlighting the practical decision‐making constraints faced by consumers. We find potential “leakage” effects in calories and nutrition when choosing a lower‐impact, plant‐forward meal. These leakage effects should be considered in future studies seeking to evaluate the environmental implications of meal substitutions in the context of broader dietary requirements.

Distinct roles of SOX9 in self-renewal of progenitors and mesenchymal transition of the endothelium - Jilai Zhao; Laura Sormani; Sebastien Jacquelin; Haiming Li; Cassandra Styke; Chenhao Zhou; Jonathan Beesley; Linus Oon; Simranpreet Kaur; Seen-Ling Sim; Ho Yi Wong; James Dight; et al. (Angiogenesis, 2024)
Regenerative capabilities of the endothelium rely on vessel-resident progenitors termed endothelial colony forming cells (ECFCs). This study aimed to investigate if these progenitors are impacted by conditions (i.e., obesity or atherosclerosis) characterized by increased serum levels of oxidized low-density lipoprotein (oxLDL), a known inducer of Endothelial-to-Mesenchymal Transition (EndMT). Our investigation focused on understanding the effects of EndMT on the self-renewal capabilities of progenitors and the associated molecular alterations. In the presence of oxLDL, ECFCs displayed classical features of EndMT, through reduced endothelial gene and protein expression, function as well as increased mesenchymal genes, contractility, and motility. Additionally, ECFCs displayed a dramatic loss in self-renewal capacity in the presence of oxLDL. RNA-sequencing analysis of ECFCs exposed to oxLDL validated gene expression changes suggesting EndMT and identified SOX9 as one of the highly differentially expressed genes. ATAC sequencing analysis identified SOX9 binding sites associated with regions of dynamic chromosome accessibility resulting from oxLDL exposure, further pointing to its importance. EndMT phenotype and gene expression changes induced by oxLDL in vitro or high fat diet (HFD) in vivo were reversed by the silencing of SOX9 in ECFCs or the endothelial-specific conditional knockout of Sox9 in murine models. Overall, our findings support that EndMT affects vessel-resident endothelial progenitor’s self-renewal. SOX9 activation is an early transcriptional event that drives the mesenchymal transition of endothelial progenitor cells. The identification of the molecular network driving EndMT in vessel-resident endothelial progenitors presents a new avenue in understanding and preventing a range of condition where this process is involved.

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Towards credible, evidence-based environmental rating ecolabels for consumer products: A proposed framework - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; Richard Murphy (Journal of Environmental Management, 2023)

Chromosome-level Genome Assembly of Acanthopagrus latus Provides Insights into Salinity Stress Adaptation of Sparidae - Jianguo Lu; Dong Gao; Ying Sims; Wenyu Fang; Joanna Collins; James Torrance; Genmei Lin; Jingui Xie; Jian Liu; Kerstin Howe (Marine Biotechnology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Meta‐Fish‐Lib : A generalised, dynamic DNA reference library pipeline for metabarcoding of fishes - Rupert A. Collins; Giulia Trauzzi; Katherine M. Maltby; Thomas I. Gibson; Frances C. Ratcliffe; Jane Hallam; Sophie Rainbird; James Maclaine; Peter A. Henderson; David W. Sims; Stefano Mariani; Martin J. Genner (Journal of Fish Biology, 2021)
The accuracy and reliability of DNA metabarcoding analyses depend on the breadth and quality of the reference libraries that underpin them. However, there are limited options available to obtain and curate the huge volumes of sequence data that are available on public repositories such as NCBI and BOLD. Here, we provide a pipeline to download, clean and annotate mitochondrial DNA sequence data for a given list of fish species. Features of this pipeline include (a) support for multiple metabarcode markers; (b) searches on species synonyms and taxonomic name validation; (c) phylogeny assisted quality control for identification and removal of misannotated sequences; (d) automatically generated coverage reports for each new GenBank release update; and (e) citable, versioned DOIs. As an example we provide a ready‐to‐use curated reference library for the marine and freshwater fishes of the U.K. To augment this reference library for environmental DNA metabarcoding specifically, we generated 241 new MiFish‐12S sequences for 88 U.K. marine species, and make available new primer sets useful for sequencing these. This brings the coverage of common U.K. species for the MiFish‐12S fragment to 93%, opening new avenues for scaling up fish metabarcoding across wide spatial gradients. The Meta‐Fish‐Lib reference library and pipeline is hosted at https://github.com/genner-lab/meta-fish-lib .

At the Turn of the Tide: Space Use and Habitat Partitioning in Two Sympatric Shark Species Is Driven by Tidal Phase - James S. E. Lea; Nicolas E. Humphries; Jenny Bortoluzzi; Ryan Daly; Rainer G. von Brandis; Ela Patel; Evan Patel; Christopher R. Clarke; David W. Sims (Frontiers in Marine Science, 2020)

Plant volatiles induced by herbivore eggs prime defences and mediate shifts in the reproductive strategy of receiving plants - Foteini G. Pashalidou; Lisa Eyman; James Sims; James Buckley; Nina E. Fatouros; Consuelo M. De Moraes; Mark C. Mescher (Ecology Letters, 2020)
Plants can detect cues associated with the risk of future herbivory and modify defence phenotypes accordingly; however, our current understanding is limited both with respect to the range of early warning cues to which plants respond and the nature of the responses. Here we report that exposure to volatile emissions from plant tissues infested with herbivore eggs promotes stronger defence responses to subsequent herbivory in two Brassica species. Furthermore, exposure to these volatile cues elicited an apparent shift from growth to reproduction in Brassica nigra , with exposed plants exhibiting increased flower and seed production, but reduced leaf production, relative to unexposed controls. Our results thus document plant defence priming in response to a novel environmental cue, oviposition‐induced plant volatiles, while also showing that plant responses to early warning cues can include changes in both defence and life‐history traits.

Characterization of Male-Produced Aggregation Pheromone of the Bean Flower Thrips Megalurothrips sjostedti (Thysanoptera: Thripidae) - Saliou Niassy; Amanuel Tamiru; James G. C. Hamilton; William D. J. Kirk; Roland Mumm; Cassie Sims; Willem Jan de Kogel; Sunday Ekesi; Nguya K. Maniania; Krishnakumari Bandi; Fraser Mitchell; Sevgan Subramanian (Journal of Chemical Ecology, 2019)

Fungal and herbivore elicitation of the novel maize sesquiterpenoid, zealexin A4, is attenuated by elevated CO2 - Shawn A. Christensen; Alisa Huffaker; James Sims; Charles T. Hunter; Anna Block; Martha M. Vaughan; Denis Willett; Maritza Romero; J. Erik Mylroie; W. Paul Williams; Eric A. Schmelz (Planta, 2018)

Exploring the Effects of Plant Odors, from Tree Species of Differing Host Quality, on the Response of Lymantria dispar Males to Female Sex Pheromones - Andrea Clavijo McCormick; Jonathan Heyer; James W. Sims; Mark C. Mescher; Consuelo M. De Moraes (Journal of Chemical Ecology, 2017)

Characterisation of agricultural drainage ditch sediments along the phosphorus transfer continuum in two contrasting headwater catchments - Mairead Shore; Phil Jordan; Per-Erik Mellander; Mary Kelly-Quinn; Karen Daly; James Tom Sims; David P. Wall; Alice Rowena Melland (Journal of Soils and Sediments, 2016)

An analysis of the sponge Acanthostrongylophora igens' microbiome yields an actinomycete that produces the natural product manzamine A - Amanda L. Waters; Olivier Peraud; Noer Kasanah; James W. Sims; Nuwan Kothalawala; Matthew A. Anderson; Samuel H. Abbas; Karumanchi V. Rao; Vijay R. Jupally; Michelle Kelly; Amala Dass; Russell T. Hill; et al. (Frontiers in Marine Science, 2014)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Australian agriculture: coping with dangerous climate change - Will Steffen; John Sims; James Walcott; Greg Laughlin (Regional Environmental Change, 2011)

Variability in Light-Use Efficiency for Gross Primary Productivity on Great Plains Grasslands - H. Wayne Polley; Rebecca L. Phillips; Albert B. Frank; James A. Bradford; Phillip L. Sims; Jack A. Morgan; James R. Kiniry (Ecosystems, 2011)

Physiological and environmental regulation of interannual variability in CO 2 exchange on rangelands in the western United States - H. WAYNE POLLEY; WILLIAM EMMERICH; JAMES A. BRADFORD; PHILLIP L. SIMS; DOUGLAS A. JOHNSON; NICANOR Z. SALIENDRA; TONY SVEJCAR; RAYMOND ANGELL; ALBERT B. FRANK; REBECCA L. PHILLIPS; KEIRITH A. SNYDER; JACK A. MORGAN (Global Change Biology, 2010)
For most ecosystems, net ecosystem exchange of CO 2 (NEE) varies within and among years in response to environmental change. We analyzed measurements of CO 2 exchange from eight native rangeland ecosystems in the western United States (58 site‐years of data) in order to determine the contributions of photosynthetic and respiratory (physiological) components of CO 2 exchange to environmentally caused variation in NEE. Rangelands included Great Plains grasslands, desert shrubland, desert grasslands, and sagebrush steppe. We predicted that (1) week‐to‐week change in NEE and among‐year variation in the response of NEE to temperature, net radiation, and other environmental drivers would be better explained by change in maximum rates of ecosystem photosynthesis ( A max ) than by change in apparent light‐use efficiency ( α ) or ecosystem respiration at 10 °C ( R 10 ) and (2) among‐year variation in the responses of NEE, A max , and α to environmental drivers would be explained by changes in leaf area index (LAI). As predicted, NEE was better correlated with A max than α or R 10 for six of the eight rangelands. Week‐to‐week variation in NEE and physiological parameters correlated mainly with time‐lagged indices of precipitation and water‐related environmental variables, like potential evapotranspiration, for desert sites and with net radiation and temperature for Great Plains grasslands. For most rangelands, the response of NEE to a given change in temperature, net radiation, or evaporative demand differed among years because the response of photosynthetic parameters ( A max , α ) to environmental drivers differed among years. Differences in photosynthetic responses were not explained by variation in LAI alone. A better understanding of controls on canopy photosynthesis will be required to predict variation in NEE of rangeland ecosystems.

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Allelochemical Potential of Callicarpa acuminata - Ana Luisa Anaya; Rachel Mata; James J. Sims; Azucena Gonz´lez-Coloma; Rocio Cruz-Ortega; Ana Guadaño; Blanca E. Hernández-Bautista; Sharon L. Midland; Griselda Ríos; Arturo Gómez-Pompa (Journal of Chemical Ecology, 2003)

Associations of maternal and umbilical cord hormone concentrations with maternal, gestational and neonatal factors (United States) - Rebecca Troisi; Nancy Potischman; James Roberts; Pentti Siiteri; Ashi Daftary; Cynthia Sims; Robert N. Hoover (Cancer Causes & Control, 2003)

Inhibition of biofilm formation and swarming of Escherichia coli by ( 5Z )‐4‐bromo‐5‐(bromomethylene)‐3‐butyl‐2( 5H )‐furanone - Dacheng Ren; James J. Sims; Thomas K. Wood (Environmental Microbiology, 2001)
The quorum‐sensing disrupter ( 5Z )‐4‐bromo‐5‐(bromomethylene)‐3‐butyl‐2(5H)‐furanone (furanone) of the alga Delisea pulchra was found to inhibit the swarming motility of Escherichia coli completely at 13 µg cm −2 (also at 20 µg ml −1 ) but did not inhibit its growth rate at 13–52 µg cm −2 or from 20 to 100 µg ml −1 . Swimming was not inhibited by the furanone at 20–40 µg ml −1 . In addition, confocal scanning laser microscopy revealed that this furanone at 60 µg ml −1 inhibited the biofilm formation of E. coli , as it decreased its thickness by 55%, reduced the number of water channels and decreased the percentage of live cells by 87%. This suggests that natural furanone may be used as a new method to control bacterial biofilms that does not involve toxicity. Furanone at 10 µg ml −1 also inhibited by 3300‐fold the quorum sensing of Vibrio harveyi via autoinducer 1 (AI‐1) and inhibited by 5500‐fold that of V. harveyi via of autoinducer 2 (AI‐2) as well as inhibited by 26 600‐fold the quorum sensing of E. coli via AI‐2; hence, this furanone is a non‐specific intercellular signal antagonist.

Photosynthesis, respiration, and net primary production of sunflower stands in ambient and elevated atmospheric CO 2 concentrations: an invariant NPP:GPP ratio? - Weixin Cheng; Daniel A. Sims; Yiqi Luo; James S. Coleman; Dale W. Johnson (Global Change Biology, 2000)
Summary The effect of elevated CO 2 on photosynthesis, respiration, and growth efficiency of sunflower plants at the whole‐stand level was investigated using a whole‐system gas exchange facility (the EcoCELLs at the Desert Research Institute) and a 13 C natural tracer method. Total daily photosynthesis (GPP), net primary production (NPP), and respiration under the elevated CO 2 treatment were consistently higher than under the ambient CO 2 treatment. The overall level of enhancement due to elevated CO 2 was consistent with published results for a typical C3 plant species. The patterns of daily GPP and NPP through time approximated logistic curves under both CO 2 treatments. Regression analysis indicated that both the rate of increase (the parameter ‘ r ’) and the maximum value (the parameter ‘ k ’) of daily GPP and NPP under the elevated CO 2 treatment were significantly higher than under the ambient CO 2 treatment. The percentage increase in daily GPP due to elevated CO 2 varied systematically through time according to the logistic equations used for the two treatments. The GPP increase due to elevated CO 2 ranged from approximately 10% initially to 73% at the peak, while declining to about 33%, as predicted by the ratio of the two maximum values. Different values of percentage increase in GPP and NPP were obtained at different sampling times. This result demonstrated that one‐time measurements of percentage increases due to elevated CO 2 could be misleading, thereby making interpretation difficult. Although rhizosphere respiration was substantially enhanced by elevated CO 2 , no effect of elevated CO 2 on R:P (respiration:photosynthesis) was found, suggesting an invariant NPP:GPP ratio during the entire experiment. Further validation of the notion of an invariant NPP:GPP ratio may significantly simplify the process of quantifying terrestrial carbon sequestration by directly relating total photosynthesis to net primary production.

Carbon budgeting in plant–soil mesocosms under elevated CO 2 : locally missing carbon? - Weixin Cheng; Daniel A. Sims; Yiqi Luo; Dale W. Johnson; J. Timothy Ball; James S. Coleman (Global Change Biology, 2000)
Summary Studies have suggested that more carbon is fixed due to a large increase in photosynthesis in plant–soil systems exposed to elevated CO 2 than could subsequently be found in plant biomass and soils –‐ the locally missing carbon phenomenon. To further understand this phenomenon, an experiment was carried out using EcoCELLs which are open‐flow, mass‐balance systems at the mesocosm scale. Naturally occurring 13 C tracers were also used to separately measure plant‐derived carbon and soil‐derived carbon. The experiment included two EcoCELLs, one under ambient atmospheric CO 2 and the other under elevated CO 2 (ambient plus 350 μL L − 1 ). By matching carbon fluxes with carbon pools, the issue of locally missing carbon was investigated. Flux‐based net primary production ( NPP f ) was similar to pool‐based primary production ( NPP p ) under ambient CO 2 , and the discrepancy between the two carbon budgets (12 g C m − 2 , or 4% of NPP f ) was less than measurement errors. Therefore, virtually all carbon entering the system under ambient CO 2 was accounted for at the end of the experiment. Under elevated CO 2 , however, the amount of NPP f was much higher than NPP p , resulting in missing carbon of approximately 80 g C m − 2 or 19% of NPP f which was much higher than measurement errors. This was additional to the 96% increase in rhizosphere respiration and the 50% increase in root growth, two important components of locally missing carbon. The mystery of locally missing carbon under elevated CO 2 remains to be further investigated. Volatile organic carbon, carbon loss due to root washing, and measurement errors are discussed as some of the potential contributing factors.

A note on the kinetics of uptake of d-glucose by the food yeast, Candida utilis - James A. Barnett; Anthony P. Sims (Archives of Microbiology, 1976)

Some physiological observations on the uptake of d-glucose and 2-deoxy-d-glucose by starving and exponentially-growing yeasts - James A. Barnett; Anthony P. Sims (Archives of Microbiology, 1976)